2020
DOI: 10.1109/tnnls.2019.2935975
|View full text |Cite
|
Sign up to set email alerts
|

Unsupervised Anomaly Detection With LSTM Neural Networks

Abstract: We investigate anomaly detection in an unsupervised framework and introduce Long Short Term Memory (LSTM) neural network based algorithms. In particular, given variable length data sequences, we first pass these sequences through our LSTM based structure and obtain fixed length sequences. We then find a decision function for our anomaly detectors based on the One Class Support Vector Machines (OC-SVM) and Support Vector Data Description (SVDD) algorithms. As the first time in the literature, we jointly train a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
85
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 230 publications
(94 citation statements)
references
References 39 publications
(129 reference statements)
0
85
0
Order By: Relevance
“…time series, deep recurrent autoencoders using long-short-term memory networks (LSTMs) (Goodfellow et al, 2016) have shown great success over conventional methods (e.g. SVM) (Ergen et al, 2017). We adapt this model for this work.…”
Section: Autoencodermentioning
confidence: 99%
“…time series, deep recurrent autoencoders using long-short-term memory networks (LSTMs) (Goodfellow et al, 2016) have shown great success over conventional methods (e.g. SVM) (Ergen et al, 2017). We adapt this model for this work.…”
Section: Autoencodermentioning
confidence: 99%
“…Few unsupervised non-visual anomaly recognition arts [35,36,28] have used autoencoders for feature extraction. However, these cannot directly fit on to spatio-temporal data.…”
Section: Related Workmentioning
confidence: 99%
“…More recently, Ergen et al [59] present a hybrid framework for variable length sequences based on LSTM and the use of either OC-SVM [43] or SVDD [77] as anomaly detectors. The novelty in the approach comes from the fact they jointly optimise the parameters of both LSTM and the anomaly detector by developing specific gradient based training methods.…”
Section: Recent Advances In Recurrent Neural Networkmentioning
confidence: 99%